PROFESIONALISME PEGAWAI NEGERI SIPIL KECAMATAN LANDASAN ULIN KOTA BANJARBARU - Ade Hermawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Civil Service Platform Ulin District of Banjarbaru professional work. The proof is the third indicator that researchers make a measure to assess the professionalism of the Civil Service Platform Ulin District of Banjarbaru namely work ability , work skills , and work experience , all of them showed good results . Efforts to increase the professionalism of the Civil Service in the District of Runway Ulin Banjarbaru done through rekreuitment employees in accordance with the needs of the organization and corruption-free , design work , arranged on the pattern of the employment relationship , work assessment carried out by an instrument Rate Job Performance Employees ( PPKP ) consisting of a Target Job employees ( SKP ) and Conduct of work , education and training of employees through leadership training , functional training and technical training , improving the discipline to enforce disciplinary rules in accordance with applicable regulations. Keyword : Professionalism, Civil Servant.